Accuracy of commercial 3D printers for the fabrication of surgical guides in dental implantology. (February 2022) - Rouzé l'Alzit, Francois; Cade, Romain; Naveau, Adrien; Babilotte, Joanna; Meglioli, Matteo; Catros, Sylvain
Highlights: This study evaluated trueness and precision of two different surgical guides (small extent = single implant and large extent = full arch) fabricated by five different commercial AM technologies (SLA, DLP, FDM, SLS and Inkjet). The small-extent SG was more accurate than the large guide, regardless of the 3D printer technology. The SLA and DLP technologies showed similar results in terms of trueness and precision for both small-extent and large-extent SG. FDM technology was the least accurate technology. Abstract: Objectives: To evaluate the accuracy of two different surgical guides (small extent = single implant and large extent = full arch) fabricated by five additive manufacturing technologies (SLA=Stereolithography, DLP= Digital Light Processing, FDM=Fused Deposition Modeling, SLS=Selective Laser Sintering, Inkjet). Methods: Overall, 72 guides (6 per type) were obtained with the different machines (SLA=Form2; DLP=Rapid Shape D40 and Cara Print 4.0; FDM=Raise 3D Pro2; SLS=Prodways P1000; Polyjet®=Stratasys J750). The guides were surface-scanned with an optical dental scanner, and the resulting files were compared with the initial design files using a surface matching software. Root Mean Square (RMS) and standard deviation were calculated, representing respectively trueness and precision. Kruskall-Wallis non-parametric test was used to compare trueness and precision between small-extent and large-extent guides and 3D printer by pairs. The threshold for significance was α=0.05, except for the comparison of printers by pairs where a Bonferroni-corrected level of 0.0033 was used. Results: Significant differences were observed for trueness and precision between small-extent and large-extent guides, regardless the printer except for DLP (trueness and precision) and SLS (precision). SLA, DLP and Polyjet® technologies showed similar results in terms of trueness and precision for both small-extend and large-extend guides ( P >0.05). Conclusions: The size affected the accuracy of CAD-CAM surgical guides. The different additive manufacturing technologies had a limited impact on the accuracy. Clinical Significance: This study is of clinical interest as it shows that the 3D printing technology (SLA/DLP) has a limited impact on 3D printed surgical guides accuracy. However, the size of the guide can have a significant impact, as small-extent guides were more accurate than large-extent guides.